The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s0266466612000746
|View full text |Cite
|
Sign up to set email alerts
|

Fast Convergence Rates in Estimating Large Volatility Matrices Using High-Frequency Financial Data

Abstract: Financial practices often need to estimate an integrated volatility matrix of a large number of assets using noisy high-frequency data. Many existing estimators of a volatility matrix of small dimensions become inconsistent when the size of the matrix is close to or larger than the sample size. This paper introduces a new type of large volatility matrix estimator based on nonsynchronized high-frequency data, allowing for the presence of microstructure noise. When both the number of assets and the sample size g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 21 publications
(31 reference statements)
1
48
0
4
Order By: Relevance
“…Several issues arise for the estimation of Σ x (t): 1. asynchronous observations of different assets; 2. microstructure noise; 3. the number of assets can be larger than the sample size. In this paper, we adopt the threshold Multi-Scale Realized Volatility Matrix estimator (threshold MSRVM) proposed by Tao et al (2013), denoted byΣ x (t), t = 1, · · · , T . The threshold MSRVM estimator has many attractive properties, for instance, it is consistent for the highdimensional integrated co-volatility matrix with the optimal convergence rate.…”
Section: Realized Covariance Matrix Estimatormentioning
confidence: 99%
See 2 more Smart Citations
“…Several issues arise for the estimation of Σ x (t): 1. asynchronous observations of different assets; 2. microstructure noise; 3. the number of assets can be larger than the sample size. In this paper, we adopt the threshold Multi-Scale Realized Volatility Matrix estimator (threshold MSRVM) proposed by Tao et al (2013), denoted byΣ x (t), t = 1, · · · , T . The threshold MSRVM estimator has many attractive properties, for instance, it is consistent for the highdimensional integrated co-volatility matrix with the optimal convergence rate.…”
Section: Realized Covariance Matrix Estimatormentioning
confidence: 99%
“…We firstly conduct data cleaning with the procedures introduced in Brownlees and Gallo (2006) and Barndorff-Nielsen et al (2009). The steps are the following: Then, we construct the threshold MSRVM estimator based on the cleaned tick-by-tick data following the steps in Tao et al (2013). We set the threshold to be 5% of the largest of the absolute value of entries in the matrix.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…When there are a large number of assets in financial practices such as asset pricing, portfolio allocation, and risk management, the volatility estimators designed for estimating a small integrated volatility matrix perform very poorly, and in fact, they are inconsistent when both the number of assets and sample size go to infinity [27]. For the case of a large number of assets, we need to impose some sparse structure on the integrated volatility matrix and employ regularization such as thresholding to obtain consistent estimators of the large volatility matrix [23,24,25]. In particular, Tao et al [23,24] investigated convergence rates of multi-scale realized volatility matrix estimator in the asymptotic framework that allows both the number of assets and sample size to go to infinity, and showed that the estimator achieves optimal convergence rate with respect to the sample size.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of a large number of assets, we need to impose some sparse structure on the integrated volatility matrix and employ regularization such as thresholding to obtain consistent estimators of the large volatility matrix [23,24,25]. In particular, Tao et al [23,24] investigated convergence rates of multi-scale realized volatility matrix estimator in the asymptotic framework that allows both the number of assets and sample size to go to infinity, and showed that the estimator achieves optimal convergence rate with respect to the sample size. This paper considers the kernel realized volatility (KRV) [4,5], the pre-averaging realized volatility (PRV) [13,18], and the multi-scale realized volatility (MSRV) [23,30] based on generalized sampling time scheme.…”
Section: Introductionmentioning
confidence: 99%